A RETROSPECTIVE STUDY TO DETERMINE THE TYPE OF COMPLICATIONS GENERATED AS A RESULT OF THYROIDECTOMY IN IRAQ - Dr. EMAD KHALID MOHAMMED; Dr. Ibrahim Mustafa Siddik (Scholar Express Journals, 2022)
BackgroundThyroidectomy aims to completely or partially remove the thyroid gland,which is located in the anterior neck area, in cases of several diseases ofthe thyroid gland.ObjectiveThis study aims to determine the type of complications generated as aresult of thyroidectomy in Iraq.Material and methodA retrospective study was conducted in Iraq on 70 patients who underwentthyroidectomy during the period from November 2020 to September 2021at different hospitals in Iraq, and demographic data were analysedaccording to IBM SOFT SPSS 22.The clinical records of the patients were accessed, from which patient datawere extracted in terms of gender, age, and development of the patientswho underwent surgery in the mentioned periodResultsthe complication which found in this study for 70 patient was(Hypocalcemia for nine patients with 12.6, Wound hematoma for sixpatients with 8.6%, External branch of superior laryngeal nerve palsy forfour patients with 5.7%ConclusionA positive statistically significant relationship was found between thefrequencies of type of thyroid surgery complications with a 0.056 p-value
Keywords: Surgery, Complications, Hypocalcemia, Thyroidectomy, Hematoma, Laryngeal.